Single nucleotide polymorphisms in the β-tubulin gene family of Ascaris lumbricoides and their potential role in benzimidazole resistance: a systematic review - Ramkhelawan, Teniel; Naidoo, Pragalathan; Mkhize-Kwitshana, Zilungile L. (Frontiers in Tropical Diseases, 2024)
Introduction The most common soil-transmitted helminthic infection is caused by Ascaris lumbricoides (A. lumbricoides). Approximately 4 billion people are at risk of infection globally. The World Health Organisation recommends the administration of benzimidazole- containing deworming drugs (Albendazole and Mebendazole) to all susceptible populations. Due to this high drug pressure, these parasites may develop resistance to current benzimidazole drugs. The β-tubulin gene family is the target gene for benzimidazole deworming drugs. This systematic review aimed to highlight work that explored the genetic mutations in the β-tubulin gene family of A. lumbricoides that are associated with potential benzimidazole resistance. Methods An electronic search of several online databases was used to extract eligible articles using specific keywords related to the topic of interest. Results The majority of ascariasis infections occur in the subtropical and tropical regions of sub-Saharan Africa, the Americas and East Asia, although not enough studies were done to extensively cover this geographical range. In the β-tubulin gene family of A. lumbricoides the mutations at codons F200Y (TTC/Phenylalanine to TAC/Tyrosine), E198A (GAG, GAA/Glutamic acid to GCG, GCA/Alanine) and F167Y (TTC, TTT/Phenylalanine to TAC, TAT/Tyrosine) were associated with potential benzimidazole resistance. Discussion Resistant mutations were found in A. lumbricoides samples at codon F167Y from Haiti, Kenya and Panama. The first evidence of the mutation at codon F200Y was observed in Brazil. The codon E198A mutation was the least prevalent and most undetected. Conclusion There is a serious shortage of studies investigating the prevalence of β-tubulin gene family mutations in A. lumbricoides populations from endemic areas; this is a serious concern as resistance will negatively impact current mass drug administration programmes.